Evaluasi Produktivitas Padi Transgenik Rojolele yang Potensial Tahan Penggerek Batang Padi Kuning Scirpophaga incertulas Wlk - Ade Nena Nurhasanah; Fatimah Zahra; Amy Estiati; Usyati Usyati; Carla Frieda Pantouw; Budi Satrio Maulana; Muhammad Taufik Hidayatv; Satya Nugroho (Institut Pertanian Bogor, 2020)
Rice yellow stem borer (YSB, Scirpophaga incertulas Wlk) is one of the most damaging rice pests in Indonesia, especially in rice growing centers in West Java. Because there is no source of resistance genes in rice or its close relatives, resistant improvement by genetic engineering is one strategy to obtain resistant rice cultivar. Previously, the cryIB::cryIAa fusion gene from Bacillus thuringiensis has been introduced into the Rojolele variety to obtain 6 transgenic rice events resistant to YSB (X22, U10, W3, Y7, Q20, and P8) and has been tested for resistance in greenhouses. This study was aimed to evaluate the transgenic rice productivity carried out in a confined field trial in field station belonging to the Center for Rice Research in Sukamandi, Subang, West Java. The procedure for the field testing followed the 1998 Guidelines for Biosafety Testing of Agricultural Biotechnology Products: Plant Seri by the Ministry of Agriculture. The parameters observed were agronomic characters (plant height, number of tillers, and number of panicles) and yield components (number of filled grains per panicle, number of empty grains per panicle, panicle length, and weight of 1000 grains). The yield was also measured by dry grain yield. The results indicated that the performance were varied among the 6 events tested. Rice events X22, W3, Y7, and P8 showed agronomic characteristics and yield components resembled Rojolele varieties, and performed well under field condition. X22 and W3 showed closest resemblance to Rojolele in terms of yield potential. Keywords: confined field trial, cryIB::cryIAa, production, rice yellow stem borrer, rojolele rice, transgenic